Inhibition of USP14 Deubiquitinating Activity as a Potential Therapy for Tumors with p53 Deficiency - Yu-Shui Ma; Xiao-Feng Wang; Yun-Jie Zhang; Pei Luo; Hui-Deng Long; Liu Li; Hui-Qiong Yang; Ru-Ting Xie; Cheng-You Jia; Gai-Xia Lu; Zheng-Yan Chang; Jia-Jia Zhang; et al. (Molecular Therapy: Oncolytics, 2020)
Functional elimination of p53 is a common feature of a large percentage of human malignancies. Here, we report the development of a pharmacological strategy aimed at restoring p53 function and its use for targeted therapy in p53-deficient mice. Specific inhibition of deubiquitinases ubiquitin-specific peptidase 14 (USP14) resulted in durable tumor regressions of autochthonous lymphomas and sarcomas in p53-deficient mice without affecting normal tissues, and therapeutic response was correlated with an increase in the ubiquitination of constitutive photomorphogenesis 9 (COP9) signalosome subunit 5 (COPS5), a key negative regulatory effector for p53. Inhibition of USP14 resulted in durable tumor regression through COPS5 deubiquitilation and a p53-dependent and -independent regulation mechanism by USP14. This series highlights the utility of proteasome deubiquitinating activity inhibition as a novel treatment paradigm for p53-deficient cancers. In addition, it provides preliminary evidence that inhibition of USP14 resulted in durable tumor regression through COPS5 deubiquitilation and p53-dependent and -independent regulation mechanism by USP14. These findings suggest that the deubiquitinating activity of the 19S regulatory particle is a new anticancer drug target for patients with p53 deficiency. Keywords: p53, COPS5, USP14, DUB, ubiquitination